Generation of Ultra‐High‐Molecular‐Weight Polyethylene from Metallocenes Immobilized onto N‐Doped Graphene Nanoplatelets. Issue 6 (25th January 2013) - Choi, Baekhap; Lee, Juno; Lee, Seungjun; Ko, Jae‐Hyeon; Lee, Kyoung‐Seok; Oh, Junghoon; Han, Jongwoo; Kim, Yong‐Hyun; Choi, Insung S.; Park, Sungjin
Abstract Catalytic natures of organometallic catalysts are modulated by coordinating organic ligands with proper steric and electronic properties to metal centers. Carbon‐based nanomaterials such as graphene nanoplatelets are used with and without N‐doping and multiwalled carbon nanotube as a ligand for ethylene polymerizations. Zirconocenes or titanocenes are immobilized on such nanomaterials. Polyethylenes (PEs) produced by such hybrids show a great increase in molecular weight relative to those produced by free catalysts. Specially, ultra‐high‐molecular‐weight PEs are produced from the polymerizations at low temperature using the hybrid with N‐doped graphene nanoplatelets. This result shows that such nanomaterials act a crucial role to tune the catalytic natures of metallocenes.